Produktivitas Kerja: Persepsi Pemberian Bonus Buruh/Pekerja Dan Pengusaha - Jonny Simamora; Pipi Susanti; Sonia Ivana Barus (PROGRESIF: Jurnal Hukum, 2021)
In addition to getting wages, there are other variables that also appear to be related to the performance of workers/labourers, namely bonuses. Work agreement contains a bonus calculation clause, then the bonus becomes mandatory and becomes the right of the worker/worker. However, if it is not contained in the work agreement, then the entrepreneur may consider that the bonus is something that is not mandatory. This of course creates a different perception between workers, employers and the government in interpreting bonuses. Whether the bonus is part of the workers/labor's rights or is the bonus only an award whose payment really depends on the good faith of the entrepreneur. This paper presents the discourse by explaining from socio-legal research because it is a study of law using a legal science approach and social science approach using a field approach. This paper reveals that the bonus arrangement itself is an important component in the working relationship between the employer/employer and the worker/labourer. Because in principle, bonuses are one way to increase company productivity.